Manhaj Bayani Ijtimai: Textual and Contextual Approach to the Quran - Ramadhani, Wali (Proceedings of International Conference on Muslim Society and Thought, 2024)
This article elaborates on two approaches to interpreting the Qur'an initiated by two Muslim figures. The Bayani approach was introduced by Amin al-Khuli, who was then perfected by his wife, Bintu Syati, in his work Tafsir Bayani. Meanwhile, the Ijtima'i approach is often based on Muhammad Abduh in explaining the verses of the Qur'an recorded in Tafsir al-Manar. This article uses a descriptive-analytical method. These two approaches are described and then analyzed. The results of this research show that: First, through the Bayani approach, the interpretation of the Qur'an goes through two stages: dirasah ma Hawla al-Qur'an (This study focuses on the study of the process of the Nuzul al-Qur'an, its collection, development, and circulation in Arab society as an object of revelation, as well as the socio-historical aspects of the Qur'an, including the intellectual, cultural, and geographical situation of Arab society in the seventh century when the Qur'an was revealed) and dirasah ma fi al-Qur'an (This study begins by examining the etymological meaning of the word, then looking for the functional meaning of the word in the Qur'an and examining the wording (murakkabat). Second, after finding the textual understanding based on the above two stages, the Qur'an interpretation must pay attention to the present context by considering humanist, social, and diversity elements. An interpreter of the Qur'an must know the various situations and conditions that surround the dynamics of social problems that develop. These considerations are executed because the Qur'an, as a human guide, should be able to answer all the problems of the Ummah that occur (past, present, and future). Therefore, the ijtima'i approach becomes important in understanding the content of the Qur'an. Third: The Bayani-Ijtima'i approach is one of the alternatives to interpreting the Quran for peace and humanity in the digital era.